Peningkatan Hasil Belajar Pendidikan Agama Katolik Melalui Problem Based Learning pada Materi Aku Citra Allah yang Unik Kelas VII SMP Negeri 7 Belimbing - Sri Eva Moderani; Brigida Intan Printina (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This research aims to improve the learning outcomes of grade VII students of SMP Negeri 7 Belimbing for the 2024/2025 school year in the subject of Catholic Religious Education through the application of the Problem Based Learning (PBL) learning model. This type of research is Classroom Action Research (PTK) which is carried out in two cycles with 2 meetings each cycle. Each cycle consists of several stages, namely planning, implementation of actions, observation and reflection. The subject matter discussed was "I am the Unique Image of Allah". The subjects in this study are grade VII students of SMP Negeri 7 Belimbing for the 2024/2025 school year consisting of 10 students. The data collection technique is in the form of test results carried out at the end of cycle I and cycle II, observation results during learning in cycle I and cycle II. The results of the study show that the application of the Problem Based Learning (PBL) learning model can improve the learning outcomes of grade VII students of SMP Negeri 7 Belimbing starting from cycle I and cycle II. In the first cycle, the percentage of student learning completeness was 80%, and in the second cycle, the percentage of completeness reached 100%. The conclusion of this study is that the application of the Problem Based Learning (PBL) learning model can improve the learning outcomes of Catholic Religious Education students in grade VII of SMP Negeri 7 Belimbing.